Confronting Cultural Constraints: A Solution to Gender Inequality in Practical Subjects in Zimbabwean Secondary Schools - MAKWANISE, Ndakaitei (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
The government of Zimbabwe has made a highly commendable effort to ensure equal access to education for boys and girls in schools. However, evidence still points to the fact that gender equality in practical subjects is far from being achieved. The study used a qualitative methodology to explore learners’ opinions, sentiments, and attitudes regarding practical subjects. This study was conducted in two secondary schools in Bulawayo- Mpopoma and Msiteli, with 350 and 225 questionnaires distributed, respectively, and 90% of the questions answered. The Msiteli surveys were completed first, followed by the Mpopoma after a two-day lull. This work discovered that, although students are willing to go through the process of selecting practical subjects, there are still elements of stereotype among boys and girls, as well as pressure from home and school, highlighting the need to confront a culture that prevents students from pursuing their desired practical subjects. Further, gender discrepancies in choosing practical disciplines exist in both schools, according to this study, as shown through questionnaires, interviews, and focus groups. This paper argues that gender inequality in schools is “structural violence”, which has a greater impact on learners’ career opportunities. A practical, holistic approach that encompasses all stakeholders is recommended in order to achieve gender equality in practical subjects.